2019
DOI: 10.3389/fpls.2019.01439
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Variation in Potyviruses

Abstract: Potyviruses (family Potyviridae, genus Potyvirus) are the result of an initial radiation event that occurred 6,600 years ago. The genus currently consists of 167 species that infect monocots or dicots, including domesticated and wild plants. Potyviruses are transmitted in a non-persistent way by more than 200 species of aphids. As indicated by their wide host range, worldwide distribution, and diversity of their vectors, potyviruses have an outstanding capacity to adapt to new hosts and environments. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 95 publications
11
124
0
Order By: Relevance
“…The terminal regions interact with adjacent subunits and provide flexibility to the virion. In serological studies, the N-terminus is dominant and, in potyviruses, is also involved with aphid interactions [22,23].…”
Section: The Origins Of the Potyviridaementioning
confidence: 99%
“…The terminal regions interact with adjacent subunits and provide flexibility to the virion. In serological studies, the N-terminus is dominant and, in potyviruses, is also involved with aphid interactions [22,23].…”
Section: The Origins Of the Potyviridaementioning
confidence: 99%
“…The N-terminal domain of potyviral CPs exposed on the surface of virus particles is highly variable among potyviruses and contains the DAG motif that is required for aphid transmission (Allison et al, 1985;Shukla et al, 1988;Dolja et al, 1991;López-Moya et al, 1999;Nigam et al, 2019). In this study, we found that the N-terminal segment amino acids 6-50 of the N-terminal domain of TuMV CP was dispensable for viral The Δ6-50 mutant produced 95% typical TuMV virions and 5% aberrant particles with an average length of 1,500 nm (Figure 2b).…”
Section: The Role Of the N-terminal Domain Of Tumv Cp In Viral Tranmentioning
confidence: 99%
“…It was shown that a single mutation can shift the outcome [14]. On the other hand, studies of PVY strains showed an exceptional diversification via nucleotide mutation and genome recombination resulting in new strains and isolates with different degrees of pathogenicity [1,[15][16][17]. Often, outcomes of the interaction in the same potato genotype are different, depending on PVY strain, as was shown for PVY N and PVY NTN in cvs.…”
Section: Introductionmentioning
confidence: 99%